1992
DOI: 10.1159/000109044
|View full text |Cite
|
Sign up to set email alerts
|

Haemostasis and Fibrinolysis after Recent Stroke

Abstract: Several measures of haemostasis and fibrinolysis were tested in 34 patients with cerebral haemorrhage and 47 patients with cerebral infarction within 11 days of the event. No significant differences were found between the two groups, but in comparison with a control group the following values were significantly elevated as the result of coagulation and fibrinolysis: fibrin monomers, thrombin-antithrombin-III, D-dimers and tissue plasminogen activator activity. In approximately 11 % of the patients the fibrin m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…Similar to our study, many studies demonstrated that high levels of the markers of coagulation activation are present in the acute phase of stroke as a result of ongoing coagulation activation (3,8,9,(24)(25)(26). However, in our study, F1+2 was higher in the stroke patients with NVAF than without NVAF.…”
Section: Discussionsupporting
confidence: 89%
“…Similar to our study, many studies demonstrated that high levels of the markers of coagulation activation are present in the acute phase of stroke as a result of ongoing coagulation activation (3,8,9,(24)(25)(26). However, in our study, F1+2 was higher in the stroke patients with NVAF than without NVAF.…”
Section: Discussionsupporting
confidence: 89%
“…These data suggest that aspirin may have, if anything, attenuated the rise in FPA found in our TIA group. As for TAT and D-dimer levels, Franke et al, 27 in a recent study of acute stroke patients, could show no difference between those who were or were not receiving aspirin.…”
Section: Discussionmentioning
confidence: 94%